Comparison of forces acting on maxillary incisors during tracheal intubation with different laryngoscopy techniques: a blinded manikin study. (25th August 2019) - Schieren, M.; Kleinschmidt, J.; Schmutz, A.; Loop, T.; Staat, M.; Gatzweiler, K.‐H.; Wappler, F.; Defosse, J.
Summary: Dental trauma is a common complication of tracheal intubation. As existing evidence is insufficient to validly assess the impact of different laryngoscopy techniques on the incidence of dental trauma, the force exerted onto dental structures during tracheal intubation was investigated. An intubation manikin was equipped with hidden force sensors in all maxillary incisors. Dental force was measured while 104 anaesthetists performed a series of tracheal intubations using direct laryngoscopy with a Macintosh blade, and videolaryngoscopy with a C‐MAC ®, or the hyperangulated GlideScope ® or KingVision ® laryngoscopes in both normal and difficult airway conditions. A total of 624 tracheal intubations were analysed. The median (IQR [range]) peak force of direct laryngoscopy in normal airways was 21.1 (14.0–32.8 [2.3–127.6]) N and 29.3 (17.7–44.8 [3.3–97.2]) N in difficult airways. In normal airways, these were lower with the GlideScope and KingVision hyperangulated laryngoscopes, with a reduction of 4.6 N (p = 0.006) and 10.9 N (p < 0.001) compared with direct laryngoscopy, respectively. In difficult airways, these were lower with the GlideScope and KingVision hyperangulated laryngoscopes, with a reduction of 9.8 N (p < 0.001) and 17.6 N (p < 0.001) compared with direct laryngoscopy, respectively. The use of the C‐MAC did not have an impact on the median peak force. Although sex of anaesthetists did not affect peak force, more experienced anaesthetists generated a higher peak force than less experienced providers. We conclude that hyperangulated videolaryngoscopy was associated with a significantly decreased force exerted on maxillary incisors and might reduce the risk for dental injury in clinical settings.